Promoting Public Participation In Development Plans The Prospect For Livable Greater Khartoum - E. M. Khair, Abbas (Universiti Sains Malaysia, 2016)

(untitled)
Public participation (PP) is important and means more to the citizens, hence is not only about development plans, but also about lives and livelihoods. It is offers citizens a perspective of their future, health, destiny, and community. As a result, PP encouraged an innovative process, that guarantees the efficiency of sustainable development plans, and promotes a sustainable new way of living in community. Sustainable development plans demands an increasing role of PP, within the frame of efficiency of sustainable planning process. Development plans in Greater Khartoum (GK), should perform a methodological process that is to be structured over distinct sequence stages, providing the development of continuous interactive, integrated and participative planning. The process of involving the public makes the results more relevant to the population’s needs, and creates a livable city. In fact, participation provides local knowledge and thus makes the planner decisions more appropriate to local specificities. This paper states a short history of public participation in development plans. The history seeks to challenge the profession’s view of participation, as simply the public processes designed and controlled by planners. Also it suggests a methodology for sustainable development plan in GK.